High entropy strategy on thermoelectric materials - Dong, Jinfeng (2023)
High-entropy materials, which consist of multiple elements occupying a single sublattice in a disordered manner, have emerged as innovative material systems with various promising applications. Many macroscopic physical properties, such as electrical transport and thermal transport, are closely related to the periodic distribution of atoms. In high-entropy compounds, the long-range periodic arrangement of atoms is broken down by the disordered distribution of various elements, which would lead to changes in physical properties. Therefore, the high-entropy idea will open new avenues for designing these functional materials with promising performance and high reliability. This perspective focuses on the high-entropy strategies of thermoelectric materials, discussing how high entropy will alter their properties. The possible routes of designing high-entropy high-performance thermoelectric materials are prospected, which can also provide enlightenment for the development of high-entropy systems in other research fields.